2006
DOI: 10.1136/oem.2005.026211
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hand eczema in female Swedish hairdressers

Abstract: Hairdressers are highly exposed to skin-damaging substances. The self-reported incidence of hand eczema was substantially higher in female hairdressers than in controls from the general population and than that found previously in register-based studies. For many individuals, onset of hand eczema occurs early in life. Only about 10% of the hand eczema cases among hairdressers would be prevented if no one with skin atopy entered the trade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
134
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(154 citation statements)
references
References 32 publications
12
134
1
4
Order By: Relevance
“…Self-employment allows individuals to achieve greater . They have a high incidence of both allergic and irritant occupational hand eczema, owing to excessive wet work and exposure to numerous substances 10,11) . They are also affected, albeit less commonly, by contact urticaria, infection, oil folliculitis, phototoxicity acne, leukoderma and malignancies 12) .…”
mentioning
confidence: 99%
“…Self-employment allows individuals to achieve greater . They have a high incidence of both allergic and irritant occupational hand eczema, owing to excessive wet work and exposure to numerous substances 10,11) . They are also affected, albeit less commonly, by contact urticaria, infection, oil folliculitis, phototoxicity acne, leukoderma and malignancies 12) .…”
mentioning
confidence: 99%
“…Incidence of hand eczema: Several studies have investigated the incidence of hand eczema in the general population (Lantinga et al, 1984;Yngveson M, 2000;Meding & Jarvholm, 2004;Brisman J et al, 1998;Meding et al, 2006;Lind, 2007;Lerbaek et al, 2007). The median incidence rate was 5.5 cases/1000 person-years (range 3.3-8.8).…”
Section: Incidence and Prevalence Of Contact Dermatitis And Contact Smentioning
confidence: 99%
“…Few studies showed that the 1-year median prevalence of hand eczema in the general population was 9.7% (11.4% among women and 5.4% among men) and that the 1-year weighted average prevalence was 9.1% (10.5% among women and 6.4% among men) (Lantinga et al, 1984;Agrup, 1969;Peltonen, 1979;Menné et al, 1982;Kavli & Forde, 1984;Meding & Swanbeck, 1987;Meding & Jarvholm, 2002;Ortengren, 1999;Meding et al, 2001;Brisman J et al, 1998;Montnemery et al, 2005;Bo et al, 2008;Fowler et al, 2006;Hald et al, 2008;Svedman et al, 2007;Lind et al, 2007).…”
Section: Prevalence Of Hand Eczemamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the occupation of hairdressing have been performed both nationally and internationally during the last 10−15 years. A number of articles stem from a Swedish context and concern respiratory symptoms 1−4) , skin symptoms 5,6) and reproduction 7−9) . Little is, however, known about the strategies that hairdressers use in their work environment to reduce health risk factors and to prevent ill health.…”
mentioning
confidence: 99%